Implications of Neuroscience for Ancient Traditional Philosophical Questions - Tarlacı, Sultan (Journal of NeuroPhilosophy, 2023)
Neurophilosophy is an interdisciplinary field of study that combines neuroscience and philosophy to better understand the nature of the mind and consciousness. It is based on the idea that advances in our understanding of the brain can shed light on longstanding philosophical questions about the nature of the self, free will, consciousness, and the relationship between the mind and the body. At its core, neurophilosophy is concerned with exploring the relationship between the brain and the mind, and understanding how neural processes give rise to mental phenomena such as consciousness, perception, thought, and emotion. It also seeks to address broader philosophical questions related to the nature of the self, free will, and the relationship between mind and body.